Advanced engineering design : an integrated approach - Benavides, Efren Moreno (Cambridge, UK : Philadelphia, PA : Woodhead Publishing, 2012)
"This book provides engineers and students with a general framework focusing on the processes of designing new engineering products. The procedures covered by the framework lead the reader to the best trade-offs to ensure maximum satisfaction of the customer's needs, meeting the lowest cost expectations, ensuring the lowest environmental impact and maximising profits and best positioning in the marketplace. Chapters discuss the engineering tools that are compatible with these goals and sustainable activity. The design process is defined in terms of operators acting over the information space: The information content is defined as a difference of entropies; Creation and destruction of entropy are defined as procedures of the design process."--Publisher's description.
1. The design process -- 2. Information, entropy and its relationship to design -- 3. Axiomatic design -- 4. Metric design -- 5. Reliability-based design -- 6. Entropy-based design -- Appendix. Statistical concepts.
Includes bibliographical references and index.
Keywords: Engineering design; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Engineering design